Bakery waste in sheep diets: intake, digestibility, nitrogen balance and ruminal parameters - França,Almira Biazon (2012)
The objective of the study was to evaluate the effects of bakery waste inclusion (0; 25; 50; 75 and 100%, DM basis) in proportion to corn meal in the energetic mixture of the concentrate on intake, digestibility, nitrogen balance and ruminal parameters in sheep. Five male lambs with body weight of 30 kg were used in a 5 × 5 Latin square design. Experimental diets were composed of concentrate and Tifton 85 (Cynodon spp.) hay in a 60:40 forage:concentrate ratio. The concentrate rations were composed of corn meal, soybean meal and bakery waste. The bakery waste:corn meal ratio corresponded to the inclusion of, approximately, 0, 7, 14, 22 and 30% (DM basis) of bakery waste in the diet. There was no effect of bakery waste inclusion on the intake and digestibility of nutrients, nor on nitrogen balance, pH values or concentrations of volatile fatty acids. However, the ammonia nitrogen concentration showed negative linear response in relation to the level of inclusion, in which each increase of 1% bakery waste promoted reduction of 0.11 mg/dL in the concentration of ammonia nitrogen. This fact may be related to the increase in ruminal availability of energy, which allows greater use of ammonia for microbial growth. Bakery waste can replace corn meal in concentrate rations for sheep.